PENGARUH POLA ASUH ORANG TUA TERHADAP KEBERRHASILAN PENDIDIKAN ANAK - Edi Saffan (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2019)
Children are a mandate from God that is entrusted to their parents. Therefore, parents are obliged to educate their children, to know God by removing all prohibitions and recommending or carrying out all His commands. Allah Almighty reminds those who believe that simply believing is not enough, so good parenting is needed in educating children. This research is motivated by the problem of phenomena that occur in the family and community environment which we have often heard that parents do not need a child to continue their education to a tertiary level, they only spend money, after finishing college they will also become unemployed, as well as perceptions. the community in their daily interactions. From this problem, we can detail some of the factors that influence it, namely the lack of enthusiasm of parents in providing increased education to their children, the lack of supporting economic factors, the lack of parents providing motivation or encouragement to children in teaching self-confidence and a sense of responsibility for their decisions. This type of research is in the form of descriptive qualitative research, with data collection techniques the writer looks for data sources from books, newspapers, magazines to be used as reference material in this paper about the influence of parenting styles on children's success. The results showed that there was an effect of parenting style on children's success.